Increased antibacterial activity by photoactivation of composites based on ZnO nanoparticles - Goncharova, Darya A.; Kulinich, Sergei A.; Nemoykina, Anna L.; Svetlichnyi, Valerii A. (Solid state phenomena)
Antibacterial composites based on linen and NPs obtained by pulsed laser ablation of a zinc target in air were synthesized at various concentrations of the active component (ZnO NPs). The surface morphology and optical properties of ZnO/linen composites were investigated by scanning electron microscopy and UV-visible spectroscopy. The antibacterial activity of ZnO/linen composites was tested on S.aureus in accordance with ISO 20743:2013. It was found that the antibacterial activity depends on the concentration of ZnO NPs. High antibacterial activity of the composites was achieved when the concentration of the active component was of 0.25 mg/cm2. At a concentration of 0.1 mg/cm2 the composites showed only a bacteriostatic effect. The use of photoactivation of composites by LED radiation of 365 nm for 10 min led to an increase in antibacterial activity about 1.5 times for the samples in both concentrations.